Sustained corticosteroid- induced mania and psychosis despite cessation: A case study and brief literature review. (November 2015) - Gable, Mary; Depry, Dwayne
Objective: Corticosteroids generally result in short-lasting neuropsychiatric symptoms following cessation, but the following case highlights an unusually long-lasting course of symptoms in a patient following near immediate cessation of medication, despite medication management and electroconvulsive therapy. The case presentation will be followed by a discussion of the presentation, treatment, and management of steroid-induced neuropsychiatric symptoms. Methods: The patient was followed from symptom onset to resolution. Results: The patient's symptom course was unusually long and required a long course of multimodal therapy. Conclusions: Corticosteroids are commonly used medications both in a wide variety of medical settings, and despite this, their neuropsychiatric effects are poorly understood. The affective and behavioral symptoms, in particular mania and psychosis, can be unpredictable and challenging to treat as in our patient, who developed a long-lasting psychotic episode on high-dose steroids despite discontinuation and treatment of nearly six months. This was despite having tolerated steroids multiple times in the past.